Mecanismos de salinização dos aqüíferos cársticos nas chapadas do Araripe e do Apodi - Mendonça, Luiz Alberto Ribeiro (2002)
Hydrochemistry is used in a study of the mechanisms of salination in two carstic aquifers, one is part of the Araripe Plateau, the other of the Apodi Plateau. In both aquifers water quality suffers seasonal changes, with electric conductivity being reduced during the rainy season. The increase of that parameter during the dry season indicates a rapid dissolution of minerals. An analysis of the indices of saturation for calcite, dolomite and anhydrite indicates that salination is mainly due the dissolution of calcite and dolomite, the principal constituents of the limestone matrix, and of bischofite, being present as trace mineral. Whereas sulfate is of little importance on of the Apodi Plateau, where gypsum is rare, dissolution of that mineral produces an increase of sulfate during the dry season in waters from the Araripe Plateau.